The book of Acts and Paul in Roman custody - Rapske, Brian (Grand Rapids, MI Eerdmans, 1994)
Includes bibliographical references and indexes
File under title so that series is shelved together.
Keywords: BIble. N.T. Acts -- criticism, interpretation, etc; Paul, the Apostle. Saint -- imprisonment